PENGARUH STRUKTUR MODAL & PERPUTARAN MODAL KERJA TERHADAP PROFITABILITAS (ROA) PADA PT CIMB NIAGA TBK PERIODE 2011-2023 - Aisya, Putri; Andhani, Destian (Journal of Research and Publication Innovation, 2024)
This study aims to determine the effect of Capital Structure & Capital Turnover on Profitability Return on Assets (ROA) at PT Cimb Niaga Tbk for the period 2011-2023 both partially and simultaneously. The method used is quantitative method. The sample used is in the form of the Financial Statements of PT Cimb Niaga Tbk. at Graha Niaga, Jakarta for 13 years. The sampling technique uses Non-Probability Sampling techniques, namely; with purposive sampling techniques. The analysis in this study used the programme, SPSS (Statistical Package for Social Science) software version 26.0. The results of the study on the Capital Structure variable (DER) had no significant effect on profitability (ROA) with the results of t_hitung < t_table or (1.094 < 2.201) then the significant value of the Capital Structure Variable of ρ value> Sig.0.05 or (0.229> 0.05). In the Working Capital Turnover variable (X2) has no significant effect on profitability (ROA) with the results of t_table < t_count or (-0.0151 < 2.201), with a significant value of the Working Capital Turnover Variable of ρ value > Sig.0.05 or (0.883 > 0.05). Based on Capital Structure & Working Capital Turnover has no significant effect on profitability (ROA) with the results of the equation F_hitung < F_tabel (0.599 < 4.100), this is also reinforced by ρ value < Sig.0.05 or (0.568 > 0.05).